Development of Ukraine territory flooding processes; Its parameters and the influence on the environmental safety level - Voloshkina, O.; Bereznitska, J. (KNUCA, 2014)
Shows the present state of development of flooding processes of Ukraine territory. Given filtration stages in the flooding the process of and methods of their calculation. The method of filtration resistance for calculating of the filtering in flooding process is analyzed. Shows the dependence between the development of flooding process and intensifying processes of landslides on Ukraine territory.
Развитие процессов подтопления на территории Украины; Оценка его параметров и влияния на уровень экологической безопасности
Keywords: environmental safety; flooding process; groundwater level; method of filtration resistance; process of landslide; экологическая безопасность; процесс подтопления; уровень грунтовых вод; метод фильтрационных сопротивлений; оползневые процессы